The Influence of Financial Literacy and Lifestyle on Retirement Readiness of Residents of Griyahasanah Cikarang Housing - Boby Maulana,; Dedi Mulyadi,; Santi Pertiwi Hari Sandi,; Uus Mohammad Darul Fadli,; Anim Zalina Azizan, (Research in Management of Technology and Business, 2024)
Financial literacy and lifestyle are key factors in their retirement preparation. The relationship between financial literacy, lifestyle, and retirement preparation in Indonesia has not been widely studied, especially in housing communities. The purpose of this study was to determine the extent to which the retirement preparation of Griyahasanah Cikarang housing residents is influenced by their lifestyle and financial literacy. A total of 50 Griyahasanah Cikarang residents were selected for this study using a purposive sampling strategy combined with a quantitative approach. The research tool for this study was a questionnaire, and SPSS was used to handle and analyze the questionnaire data. The findings of the analysis showed that although lifestyle also has a positive impact on retirement preparation, financial literacy also has a beneficial impact.